Bioactive Fraction of Annona reticulata Bark (or) Ziziphus jujuba Root Bark along with Insulin Attenuates Painful Diabetic Neuropathy through Inhibiting NF-κB Inflammatory Cascade - Kandimalla, Raghuram; Dash, Suvakanta; Kalita, Sanjeeb; Choudhury, Bhaswati; Malampati, Sandeep; Devi, Rajlakshmi; Ramanathan, Muthiah; Talukdar, Narayan C.; Kotoky, Jibon (Frontiers in Cellular Neuroscience, 2017)
The present study explains the neuroprotective ability of bioactive fractions of Annona reticulata bark (ARB) and Ziziphus jujuba root bark (ZJ) along with insulin against diabetic neuropathy. By using different solvents of increasing polarity ARB and ZJ were undergone for bioactive guided fractionation. The neuroprotective ability of the all the plant fractions were tested against H2O2 induced toxicity in SHSY5Y neuroblastoma cell lines and DRG neuronal cells. Among all the fractions tested, the methanol extract of ARB and ZJ (ARBME & ZJME) and its water fractions (ARBWF & ZJWF) exhibited significant neuroprotection against H2O2 induced toxicity in SHSY5Y cells and DRG neuronal cells. Further both the active fractions were tested against streptozotocin (55 mg/kg i.p.) induced diabetic neuropathy in male Wistar rats. Body weight changes, blood glucose levels and pain threshold through hot plate, tail immersion, cold plate and Randall-Sillitto methods were measured throughout the study at weekly interval. After completion of the drug treatment period, all the animals were sacrificed to measure the sciatic nerve lipid peroxidation, antioxidative enzyme levels (SOD, catalase, and GSH) and cytokine levels (IL-1β, IL-6, IL-10, TNF-α, iNOS & NFκB) through ELISA and western blotting analysis. Results of this study explain that ARBME, ZJME, ARBWF & ZJWF along with insulin potentially attenuate the thermal, mechanical hyperalgesia and cold allodynia in diabetic neuropathic rats, where insulin treatment alone failed to diminish the same. Reduction of sciatic nerve oxidative stress, NF-κB and iNOS mediated inflammatory cascade and normalization of abnormal cytokine release confirms the possible mechanism of action. The present study confirms the neuroprotective ability of ARB and ZJ against painful diabetic neuropathy through inhibiting oxidative stress and NF-κB inflammatory cascade.